A survey of nurses' experience integrating oncology clinical and academic worlds - Kristen R. Haase; Fay J. Strohschein; Tara C. Horill; Leah K. Lambert; Tracy L. Powell (Wiley, 2021)
Abstract Aim To better understand how oncology nurses (a) navigate graduate studies; (b) perceive the impact of their academic work on their clinical practice, and vice versa; and (c) engage with clinical settings following graduate work. Design Interpretive descriptive cross‐sectional survey. Methods A qualitative exploratory web‐based survey exploring integration of graduate studies and clinical nursing practice. Results About 87 participants from seven countries responded. 71% were employed in clinical settings, 53% were enrolled in/graduated from Master's programs; 47% were enrolled in/graduated from doctoral programs. Participants had diverse motivations for pursuing graduate studies and improving clinical care. Participants reported graduate preparation increased their ability to provide quality care and conduct research. Lack of time and institutional structures were challenges to integrating clinical work and academic pursuits. Conclusions Given the many constraints and numerous benefits of nurses engaging in graduate work, structures and strategies to support hybrid roles should be explored.